Backlit images enhancement using global tone mappings and image fusion. Issue 2 (1st February 2020) - Buades, Antoni; Lisani, Jose‐Luis; Petro, Ana Belen; Sbert, Catalina
Abstract : The authors present a method for the enhancement of backlit images, i.e. images in which the main source of light is behind the photography subject. These images contain, simultaneously, very dark and very bright regions. In this situation, a single tone mapping function is unable to enhance the whole image. They propose the use of several such tone mappings, some of them enhancing the dark regions while others enhancing the bright regions, and then the combination of all these results using an image fusion algorithm. Qualitative and quantitative results confirm the validity of the proposed method.